Математичні методи фільтрації зображень - Фірстов, М. В.; Грицунов, О. В. (ХНУРЕ, 2019)
This work is devoted to the issue of increasing image quality using mathematical methods. Also, two algorithms of filtering and theirs advantages are described and illustrated. Methods are widely applicable in modern electronic devices nowadays.
Keywords: Математичні методи фільтрації зображень